HUBUNGAN IMT, USIA DAN KEBIASAAN MEROKOK TERHADAP KEJADIAN HIPERTENSI PADA NELAYAN KUB PONDOK LAYAR: Relationship Between Body Mass Index, Age, and Smoking Habit Among Hypertension in Fisherman Kub Pondok Layar - Siti Mufaidah; Ayik Mandagi (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2019)
ABSTRACT WHO has identified hypertension as a major cause of cardiovascular death in the world. Factors that increase risk includes age, being overweight, smoking, and alcohol use. Purpose: this study aims to analyze the relationship between Body Mass Index (BMI), age, and smoking habits with the incidence of hypertension in KUB Pondok Layar fishermen. Methods: This study was analytical with a cross sectional design in January 2019, the population was all members of the Pondok Layar KUB fishermen of 90 peoples. Total samples of this study are 49 respondents with Simple Random Sampling technique. Data were analyzed by Chi Square test. Results: The incidence of hypertension in Pondok Layar KUB fishermen based on blood pressure measurements was 24.5%, which is 18.4% at type 1 and 6.1% at type 2. The majority of fishermen had started smoking before the age of 18 th (62.5%), had been smoking for more than 15 years at 77.5%, and consumed more than 12 cigarettes in a day is 45%. Age variables (CI=95%; P=0.024; OR=0.141) and BMI (CI=95%; P=0.008; OR=0.170) had a significant relationship to the incidence of hypertension in KUB Pondok Layar fishermen. Smoking habits variable (CI=95%; P=0.383), age of starting smoking (CI=95%; P=0.546), smoking time (CI=95%; P=0.209) and number of ciga rettes smoked per day (CI=95%; P=0.118) did not have a significant relationship to the incidence of hypertension in KUB Pondok Layar fishermen. Conclution: There is a significant relationship between age and BMI on the incidence of hypertension in KUB Pond ok Layar fishermen. It is recommended that fishermen need to regularly control their blood pressure and weight so that hypertension can be prevented early